2006
DOI: 10.1007/s10750-005-1233-y
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Sensitivity of Phytoplankton Communities to Changes in Water Temperature and Nutrient Load, in a Temperate Lake

Abstract: Freshwater lakes are biologically sensitive to changes in the surrounding environment and the impacts that such changes have on their water quality are of considerable ecological, recreational and economic importance. In this study the phytoplankton community model, PROTECH, was used to experiment with the effects of elevated temperatures and increased nutrient load on phytoplankton succession and productivity. The response of a phytoplankton community to combined incremental changes in these drivers was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
161
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(184 citation statements)
references
References 10 publications
19
161
1
3
Order By: Relevance
“…It is relatively shallow, with a mean depth of 5.3 m and a maximum depth of 19.0 m (Ramsbottom, 1976). Thermal stratification is episodic and readily broken down, and the average annual retention time is short, c. 19 days (Thackeray et al, 2006). Based on the annual average concentration of phytoplankton chlorophyll-a (13.4 mg m -3 , Thackeray et al, 2006), Bassenthwaite Lake may be considered eutrophic (OECD, 1982).…”
Section: Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is relatively shallow, with a mean depth of 5.3 m and a maximum depth of 19.0 m (Ramsbottom, 1976). Thermal stratification is episodic and readily broken down, and the average annual retention time is short, c. 19 days (Thackeray et al, 2006). Based on the annual average concentration of phytoplankton chlorophyll-a (13.4 mg m -3 , Thackeray et al, 2006), Bassenthwaite Lake may be considered eutrophic (OECD, 1982).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Thermal stratification is episodic and readily broken down, and the average annual retention time is short, c. 19 days (Thackeray et al, 2006). Based on the annual average concentration of phytoplankton chlorophyll-a (13.4 mg m -3 , Thackeray et al, 2006), Bassenthwaite Lake may be considered eutrophic (OECD, 1982). Estimates of the relative importance of the sources for nutrients entering the lake suggest that approximately 60% of the total annual load comes from anthropogenic sources (treated sewage waste) with the rest derived from the catchment (Thackeray et al, 2006).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct effects, such as rising temperatures, and indirect effects, such as intensified stratification, favor cyanobacterial blooms. Increased water temperature is expected to give cyanobacteria a selective advantage over competing phytoplankton because of the high optimal growth temperature of cyanobacterial species (Elliott et al, 2006;Jöhnk et al, 2008). Laboratory studies on Microcystis aeruginosa have demonstrated increasing growth rates with increasing temperatures from 20 to 32 C (van der Westhuizen and Eloff, 1985;Watanabe and Oishi, 1985;Imai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%